2018
DOI: 10.1145/3274327
|View full text |Cite
|
Sign up to set email alerts
|

Fake Cures

Abstract: Social media's unfettered access has made it an important venue for health discussion and a resource for patients and their loved ones. However, the quality of the information available, as well as the motivations of its posters, has been questioned. This work examines the individuals on social media that are posting questionable health-related information, and in particular promoting cancer treatments which have been shown to be ineffective (making it a kind of misinformation, willful or not). Using a multi-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(30 citation statements)
references
References 79 publications
1
27
0
2
Order By: Relevance
“…A few methods and tools for detecting misinformation on SM, particularly during a health crisis, have been proposed and are usually focused on specific topics and diseases (eg, Ebola and Zika) [28,29]. They typically strive to identify the characteristics of misinformation, while neglecting the factors that indicate trustworthy tweets.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A few methods and tools for detecting misinformation on SM, particularly during a health crisis, have been proposed and are usually focused on specific topics and diseases (eg, Ebola and Zika) [28,29]. They typically strive to identify the characteristics of misinformation, while neglecting the factors that indicate trustworthy tweets.…”
Section: Introductionmentioning
confidence: 99%
“…Most health studies on Twitter collect their data by using specific keywords [28,29,48-52] or from tweets authored by specific health stakeholders, such as health organizations [5,22,53-58]. However, it appears that most studies that analyze Twitter for health using specific keywords have not analyzed the types of users who post the tweets [28,29,48-52]; it is known from other studies that there are different types of users and they share different types of information or hold different attitudes toward specific health issues [59-62]. For example, a number of studies performed tweet extraction using keywords to identify public concerns during the Zika outbreak [48-52].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be possible to automate some or all of the techniques used in this study (e.g., identifying condition/advice pairs) in order to assess health information quality on social platforms in real‐time. Similar efforts have been used to automatically identify users who are likely to share health misinformation (Ghenai & Mejova, ), but identifying the quality of advice itself in real‐time has several advantages that are also worth pursuing.…”
Section: Discussionmentioning
confidence: 99%
“…However, miscommunication is critical. The work in [95] addressed the misinformation about unverified "cures" of cancer that can be found in tweets on the Twitter social network (Twitter Inc., San Francisco, CA, USA). Interestingly, the study suggested that users propagating the fake cures used a sophisticated language: they have knowledge about the medical domain but are not patients affected by this illness.…”
Section: User-centered Designmentioning
confidence: 99%